EUDR Coffee Check: A Tool to Support the Coffee Sector to Become Compliant with the European Union Regulation on Deforestation-Free Products (EUDR) - Pia Rothe; Ilknur Celik Schoreels; Phuntsho Phuntsho; Jan Henke (Proceedings)
Due to the European Regulation on Deforestation-Free Products (EUDR), coffee and other commodities and their derived products from deforested areas will be prohibited from being placed on the European Union (EU) market starting in December 2024. With the “EUDR Coffee Check”, a comprehensive tool was developed, in collaboration with the German Coffee Association (DKV), combining a database solution with automated analysis methodologies, combined with a web-frontend, to support the EUDR compliance of the coffee industry. The tool supports the gathering of verifiable information to ensure that coffee is deforestation-free after the 31 December 2020 EUDR cutoff date. To determine deforestation-free status, deep learning-based mapping methods on satellite imagery along with open access local and global datasets were applied to develop a 2020 forest reference map that aligns with the defined EUDR forest categories and the cutoff date. The tool can be used to conduct automatic deforestation checks by comparing coffee farm locations with reference forest maps from 2020 and raises a potential deforestation alert. Potential deforestation alerts are identified as critical cases based on the annually updated series of land use changes and/or deforestations observed within the base 2020 forest areas after the cutoff date. The tool also allows users to conduct a structured risk assessment of the provided geo-coordinates of production areas and the supply chain to document the complete exercise of the required EUDR due diligence process. The tool uses internationally recognized indices and statistics, such as UNDP, UNICEF, World Bank, and many more, to calculate a risk score to evaluate governance and human rights risks such as child labor, forced labor, or corruption associated with the sourcing regions. The presence of forests, deforestation risk, and maps providing information on the protected areas of indigenous people are used to identify the coffee production areas’ proximity and relative risk exposure to provide a full picture of the risk factors in line with the EUDR requirements. In addition to the detailed analysis of deforestation risk alerts, the EUDR Coffee Check provides a questionnaire that guides the user through the structured process to supplement the risk assessment and documentation of legality. Following focused questions and providing potential answers, the user is enabled to evaluate the risk for non-compliance according to the exact requirements of the EUDR and provides guidance on risk mitigation measures, such as the implementation of internal due diligence strategies, the usage of third-party verification schemes to increase reliability through on-site audits, or the usage of traceability platforms. The developed EUDR Coffee Check supports companies to comply with the EUDR due diligence obligations by analyzing, documenting, and reporting on individual shipments and the associated production areas and can be used by operators, traders, or any actor along the supply chain, including authorities, to control the checks at their discretion. The tool is offered at a nominal fee structure based on a customized term of usage.